2020
DOI: 10.1177/1468017320940644
|View full text |Cite
|
Sign up to set email alerts
|

Mental health among the Hmong population in the U.S.: A systematic review of the influence of cultural and social factors

Abstract: Summary As refugees of the war in Southeast Asia, Hmong experienced various traumatic events. Evidence suggests the persistence of psychiatric disorders related to trauma in refugees even after prolonged resettlement in their host country. This systematic review aimed to summarize the mental health literature on the Hmong population with a focus on cultural and social factors. The databases PsycINFO, PsycARTICLES, Social Services Abstracts, Web of Science, and PubMed were reviewed for peer-reviewed articles pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…Concerning the specific objective [ 3 ]; analyzing the relationship between mental health and gender, the category used as a basis was that of “male.” As can be seen, belonging to the “female” category is significantly associated with an increase in the GFI score (β= 0.066; p < 0.001), being indicative of worse mental health regarding the “male” gender (β= 0.234; p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the specific objective [ 3 ]; analyzing the relationship between mental health and gender, the category used as a basis was that of “male.” As can be seen, belonging to the “female” category is significantly associated with an increase in the GFI score (β= 0.066; p < 0.001), being indicative of worse mental health regarding the “male” gender (β= 0.234; p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Here we also see the violence of psychology where a majority of research on HMong mental health was published soon after their arrival to the United States and noted high rates of PTSD, depression, and anxiety in the context of dislocation and acculturative stress (see reviews of research by Lee, 2013; Vang et al, 2020). 3 Vang et al’s (2020) systematic review of research identified barriers to care, including stigma, communication, mental health literacy, and lack of cultural brokers; these factors largely place emphasis on a cultural difference explanatory model even as it addresses social factors. This focus is evident in attempts to increase the awareness of HMong culture, such as the widely read The Spirit Catches You and You Fall Down that has become a canonical text for producing cultural competence in health care professions (Taylor, 2003).…”
Section: The Intersection Of Politics Psychology and Violence In Scho...mentioning
confidence: 98%
“…Similarly, white and colonial lenses have also distorted understandings of HMong psychology and limited its contours by singularly focusing on HMong peoples as objects of trauma and tragedy. Here we also see the violence of psychology where a majority of research on HMong mental health was published soon after their arrival to the United States and noted high rates of PTSD, depression, and anxiety in the context of dislocation and acculturative stress (see reviews of research by Lee, 2013;Vang et al, 2020). 3 Vang et al's (2020) systematic review of research identified barriers to care, including stigma, communication, mental health literacy, and lack of cultural brokers; these factors largely place emphasis on a cultural difference explanatory model even as it addresses social factors.…”
Section: The Intersection Of Politics Psychology and Violence In Scho...mentioning
confidence: 98%
See 1 more Smart Citation
“…While Hmong have experienced many gains over the last 46 years, many continue to be underemployed, under educated, live in poverty, and face overt and covert discrimination and violence due to racism and xenophobia. Hmong face challenges such as severely unaddressed and untreated behavioral health issues (Lee & Chang, 2012;Vang et al, 2020;Vang & Bogenschutz, 2011), increasing chronic health conditions (Chen et al, 2013;Fang & Steward, 2018), barriers to adaptation (i.e., gender role conflicts) (Thor, 2020), and an array of diminished social support, poor economic well-being, and educational disparities (Pew Research Center, 2020). Hmong also vary in terms of their acculturation to U.S. society.…”
Section: Background Of Hmong Americansmentioning
confidence: 99%